Metodologias Ativas e Preceptoria no SUS: uma proposta ara o fortalecimento do COAPES de Santo Antônio de Jesus - Ba - Almeida, Tatiane Santos Couto de; Cunha, Carla de Magalhães; Souza, Ionara Magalhães de; Souza, Nívia Maria Oliveira de; Paz, Camila Torres da; Nascimento, Hozana Vieira dos Santos; Freitas, Flávia; Santos, Rogério Lima dos; Barbosa, Deise Santana de Jesus (Revista Acadêmica GUETO, 2024)
Projeto